2020
DOI: 10.3168/jds.2019-17514
|View full text |Cite
|
Sign up to set email alerts
|

Influence of proportion of wheat in a pasture-based diet on milk yield, methane emissions, methane yield, and ruminal protozoa of dairy cows

Abstract: Wheat is the most common concentrate fed to grazing dairy cows in Australia, but no studies have examined the effects of wheat proportion in a pasture-based diet on milk production and methane emissions. In this 47-d experiment, 32 Holstein dairy cows were offered 1 of 4 diets during d 1 to 36. Cows in each of the dietary treatment groups were individually offered no wheat (W0) or wheat at 3 kg of dry matter (DM)/d (W3), 6 kg of DM/d (W6), or 9 kg of DM/d (W9). The remainder of the diet was 2.2 kg of DM of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
0
18
1
Order By: Relevance
“…Methane yield (g/kg DMI) versus ruminal acetate, propionate and butyrate as mol per 100 mol of total volatile fatty acids from 215 cow records across 24 diets[24][25][26][27][28][29][30]. Solid lines are linear or reciprocal trend lines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Methane yield (g/kg DMI) versus ruminal acetate, propionate and butyrate as mol per 100 mol of total volatile fatty acids from 215 cow records across 24 diets[24][25][26][27][28][29][30]. Solid lines are linear or reciprocal trend lines.…”
mentioning
confidence: 99%
“…Combined methane yield (MY, g/kg DM) data from seven previously conducted experiments[24][25][26][27][28][29][30] plotted against ruminal fatty acid ratio A/P, (A + B)/P, and 1/P, with linear equations fitted by linear mixed effects meta-analysis (solid line).…”
mentioning
confidence: 99%
“…To date, efforts have focussed predominantly on increasing productivity through intensification and technological refinement [ 96 ]. The latter includes improving feed digestibility, type and additives to reduce enteric emissions, and changes to manure management such as acidification or fully recoupling manure recycling [ 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. As a consequence, the US now produces 60% more milk with 80% fewer cows than in 1944 [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, other studies reported a decrease of 10% of the GHG emissions per kg of milk produced between mixed systems (0.92 CO 2 eq/kg milk) and grazing systems (1.02 CO 2 eq/kg milk) (Styles et al, 2018). However, grazing systems in Latin America are characterized for low dairy production (2 -19 kg milk/cow/d; Sainz-Sánchez et al, 2017;Marín-Santana et al, 2020;Alvarado-Bolovich et al, 2021) in comparison with other regions such as New Zealand (18 -22 kg milk/cow/d; Bryant et al, 2017) or Australia (30 kg milk/cow/d; Moate et al, 2020) with a pastoral culture, which can explain the differences in the CF per kg of milk.…”
Section: Production Systemmentioning
confidence: 99%